Clinical Presentation and Laboratory Diagnostic Work-Up of a Horse with Tick-Borne Encephalitis in Switzerland - Nathalie Fouché (Viruses, 2021)
Tick-borne encephalitis is an important viral tick-borne zoonosis in Europe and Asia. The disease is induced by tick-borne encephalitis virus (TBEV). This report describes a 16-year-old Warmblood gelding presenting with sudden onset of lethargy, ataxia, and muscle fasciculations on the nostrils, the lips, and the eye lids as the most important clinical findings. The horse further had a mild facial nerve paralysis with drooping of the right upper and lower lip. Diagnosis was based on paired serum samples using TBEV-ELISAs revealing high serum IgM in the first sample with normal IgM in the second sample and an increase in serum IgG and neutralizing antibodies, indicating acute and recent infection. TBEV was confirmed by a virus-neutralization test, revealing a fivefold increase in antibodies 32 days after of the onset of clinical signs. Although the specific PCR on cerebrospinal fluid (CSF) was negative, TBEV-specific IgG and IgM were identified in the CSF of the horse. Treatment consisted of anti-inflammatory and anti-oxidative treatment and the horse recovered with a mild drooping of the right nostril as the only remaining clinical sign. TBEV infection is a potential differential diagnosis of neurological disease in horses living in endemic areas and this is the first report to describe the diagnostic criteria in a horse as recommended in humans with suspected TBEV infection.